Method of lactate elevation does not affect the determination of the lactate minimum - Smith, M. F.; Balmer, J.; Coleman, D. A.; Bird, S. R.; Davison, R. C. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The aim of the study was to examine the effects of different lactate elevation protocols on the determination of the lactate minimum (Lac(min)) point. METHODS: Eight highly trained racing cyclists each completed four continuous ramp lactate minimum tests using the following blood lactate elevation protocols: 1) continuous ramp maximal aerobic power (RMP(max)) assessment, 2) 30-s maximal sprint, 3) 40-s maximal sprint, and 4) two 20-s maximal sprints separated by a 1-min recovery. Each blood lactate elevation protocol was followed by a 5-min active recovery leading into a continuous ramp test commencing at a power of 60% of RMP(max), using a 6 W x min ramp rate, lasting 15 min. RESULTS: Peak [La](b) values were significantly higher (P > 0.05) after the RMP(max) compared with all other protocols and higher in the 40-s versus 30-s sprint. However, by the start of Lac(min) ramp, [La](b) after the RMP(max) was no longer higher than the 40-s sprint, but Lac(min) [La](b) was similar for all protocols. This resulted in no differences in the total decline of [La](b) measured as a percentage from the highest to the lowest value. At Lac(min) point, there were no significant differences in power (P > 0.05), but heart rate was higher in the RMP versus 2 x 20 s and VO(2) was significantly higher after the 40 s compared with the 2 x 20 s protocol. CONCLUSION: This study demonstrated that the determination of lactate minimum power in cycling is not dependent upon the lactate elevation protocol.